New polymorphic sites within ornithine transcarbamylase gene : population genetics studies and implications for diagnosis - Azevedo, Luísa; Stolnaja, Larisa; Tietzeová, Evženie; Hřebíček, Martin; Hrubá, Eva; Vilarinho, Laura; Amorim, António; Dvořáková, Lenka (Molecular genetics and metabolism, 2003)
Ornithine transcarbamylase (OTC) deficiency, transmitted as an X-linked trait, is the most common disorder of the urea cycle. At least 3.5% out of more than 230 mutations consist of large gene deletions, involving one or more exons. Only in 78% of OTC patients the diagnosis was confirmed on DNA level. We analysed OTC intragenic polymorphisms and haplotypes, in an attempt to contribute to the clarification of unresolved cases, in three populations (Czech, Portuguese, and Mozambican) and identified six novel nucleotide changes, all of them occurring with frequency higher than 12.5% in Europeans. Five of these polymorphisms occur with a significant frequency also in Africans. The number and frequency of haplotypes defined with the newly reported markers differ in individual populations.
Keywords: Base Sequence; Genotype; polymerázová řetězová reakce; Polymerase Chain Reaction; Genetic Markers; lidé; Molecular Sequence Data; genotyp; DNA primery; ornithinkarbamoyltransferasa; Genetics, Population; Ornithine Carbamoyltransferase; molekulární sekvence - údaje; Male; polymorfismus genetický; sekvence nukleotidů; DNA Primers; genetické markery; mužské pohlaví; Polymorphism, Genetic; populační genetika; Humans